Development and test verification of air temperature model for Chinese solar and Spainish Almeria-type greenhouses - Sanchez-Molina, Jorge Antonio; Ming, Li; Rodriguez, Francisco; Guzman, Jose Luis; Hui, Wang; Xinting, Yang (International Journal of Agricultural and Biological Engineering, 2017)
Growth can be defined as an increment in biomass or an increment in weight or height of the organs of the plant influenced by physiological processes. Many of these processes have their limits genetically determined, but climate and irrigation play an important role. Because of its importance, microclimate has been extensively studied in the modeling as a surrounding condition which is imposed by the exterior climate. The main objective of this work was to develop a temperature model based on the energy balance dynamics at two different greenhouse locations - South - eastern Spain and Northern China, and the traditional structures of Chinese solar greenhouse and Almería-type multi-span greenhouse were taken into account. The final model was developed by combining the external conditions, the actuator influence and the crop growth, where the temperature is influenced by soil, crop, cover, actuators, back wall and greenhouse geometry. The model took into account the energy lost by convective and conductive fluxes, as well as the energy supplied by solar radiation and heating systems. The soil and the back wall are the main media for energy storage. The temperature dynamic was determined by a physical model, which considered the energy balance from a holistic point of view - as a sub-model for a customizable interface among the external climate, the plant and the greenhouse system. The influences of different subsystems included in the temperature model were analyzed and evaluated. The results showed a high R2 value of 0.94 for Beijing and 0.95 for Almeria, and the average error was low, of which the MAE and RMSE were 0.71 and 1.365 for Almeria and 0.62 and 1.102 for Beijing, respectively. Thus, the model can be considered as a powerful tool for control design purposes in microclimate systems. Keywords: air temperature model, Chinese solar greenhouse, Spanish Almería-type greenhouse, energy balance dynamics, microclimate DOI: 10.25165/j.ijabe.20171004.2398 Citation: Sanchez-Molina J A, Li M, Rodriguez F, Guzman J L, Wang H, Yang X T. Development and test verification of air temperature model for Chinese solar and Spainish Almeria-type greenhouses. Int J Agric & Biol Eng, 2017; 10(4): 66–76.